Copper on carbon materials: stabilization by nitrogen doping. Issue 21 (17th May 2017) - Bulushev, Dmitri A.; Chuvilin, Andrey L.; Sobolev, Vladimir I.; Stolyarova, Svetlana G.; Shubin, Yury V.; Asanov, Igor P.; Ishchenko, Arcady V.; Magnani, Giacomo; Riccò, Mauro; Okotrub, Alexander V.; Bulusheva, Lyubov G.
Abstract : N-doping of carbon support prevents sintering of Cu and provides its high catalytic activity in H2 formation from formic acid. Abstract : The applicability of Cu/C catalysts is limited by sintering of Cu leading to deactivation in catalytic reactions. We show that the problem of sintering could be resolved by N-doping of the carbon support. Cu nanocatalysts with 1 at% of metal were synthesized by Cu acetate decomposition on N-free and N-doped (5.7 at% N) mesoporous carbon supports as well as on thermally expanded graphite oxide. Catalytic properties of these samples were compared in hydrogen production from formic acid decomposition. The N-doping leads to a strong interaction of the Cu species with the support providing stabilization of Cu in the form of clusters of less than 5 nm in size and single Cu atoms, which were observed in a significant ratio by atomic resolution HAADF/STEM even after testing the catalyst under harsh conditions of the reaction at 600 K. The mean size of the obtained Cu clusters was by a factor of 7 smaller than that of the particles in the N-free catalyst. The N-doped Cu catalyst possessed good stability in the formic acid decomposition at 478 K for at least 7 h on-stream and a significantly higher catalytic activity than the N-free Cu catalysts. The nature of the strongly interacting Cu species was studied by XPS, XRD and other methods as well as by DFT calculations. The presence of single Cu atoms in the N-doped catalysts should be attributed to their strong coordination by pyridinic nitrogen atoms at the edge of the graphene sheets of the support. We believe that the N-doping of the carbon support will allow expanding the use of Cu/C materials for different applications avoiding sintering and deactivation.